The Nutritional Composition of Maca in Hypocotyls (Lepidium meyenii Walp.) Cultivated in Different Regions of China - Longfei Chen; Jieying Li; Liuping Fan (Journal of Food Quality)
Maca (Lepidium meyenii Walp.) was introduced to China in the recent two decades. Proximate compositions and secondary metabolites in dried maca tuber powders of different cultivation areas and colour types were analyzed and compared in order to provide the scientific guideline for its application. Cultivation region significantly affects the compositions of maca. The protein content of maca ranged from 9.31% to 21.02% by dry basis of maca powders and Xiaopingba-Y, Yulong-Y, and Pamirs-Y have the higher protein contents. The essential amino acids (EAA) contents ranged from 189.19 to 312.90 mg/g protein. The crude lipid content of different maca ranged from 0.59% to 1.00% and has no significant difference (P>0.05). The total dietary fiber (TDF) contents ranged from 17.82% to 26.00% and soluble dietary fiber (SDF) ranged from 2.46% to 7.88%, respectively. Maca samples were rich in Na, Mg, Ca, and K elements which ranged 138.3–187.8, 625.2–837.2, 3838.9–4502.7, and 5394.8–8063.3 mg/kg dry matter (DM). Xiaopingba-Y has the highest benzyl glucosinolate content which was 2.31 mg/g DM. Peru-Y and Xiaopingba have the higher contents of total alkaloids contents which was 2.61 and 2.56 mg/kg DM. Yongsheng-Y, Yulong-Y, and Pamirs-Y were rich in N-benzyl hexadecanamide contents, which were 0.164, 0.174, and 0.173 mg/g DM, respectively. Significant higher protein, total dietary fiber, insoluble dietary fiber, total alkaloids, and benzyl glucosinolate contents were found in purple and black maca compared to yellow maca in Pamirs, while there was no significant difference in N-benzyl hexadecanamide content.